One-year follow-up of transcoronary sinus administration of autologous bone marrow in patients with chronic refractory angina - Vicario, Jose (2005)
Purpose: Based on our preclinic studies with autologous unfractionated bone marrow (AUBM) via coronary sinus with transitory occlusion, a clinic study in patients with chronic refractory angina was designed. The objectives were to evaluate tolerance of the procedure, safety, and feasibility with 1 year follow-up. Methods and materials: Clinical study with inclusion and exclusion criteria defined by an Independent Clinical Committee was carried out. Fifteen patients underwent transcoronary sinus administration with a 15-min occlusion of freshly aspirated and filtered AUBM (60–120 ml). Feasibility was evaluated with Seattle Angina Questionnaire (SAQ), Canadian Cardiovascular Society (CCS) angina classification, perfusion dipyridamole, and coronary angiography. Results: There were no changes in the tolerance parameters. There were no deaths or myocardial infarction during the follow-up. Three patients were readmitted into the hospital. During the follow-up, one patient was diagnosed with cancer of the lung. Improvement of 30% in the quality of life was evaluated by SAQ. The CCS angina classification showed that the mean angina class was 3.0F0.53 at baseline, which improved to 1.6F0.63 at 1 year ( Pb.001). Perfusion imaging (core lab) showed improvement in 12 of 15 patients, with a mean improvement of 40.9% at rest (22 vs. 13) ( Pb.01) and 45.3% at stress (26.5 vs. 14.5) ( Pb.05). Coronary angiography showed more collateral vessels in 10 of 15 patients. Conclusions: We can conclude that AUBM via coronary sinus is feasible in patients with chronic refractory angina after 1 year follow-up, and it appears to be safe. Based on our preclinic studies with autologous unfractionated bone marrow (AUBM) via coronary sinus with transitory occlusion, a clinic study in patients with chronic refractory angina was designed. The objectives were to evaluate tolerance of the procedure, safety, and feasibility with 1 year follow-up. Methods and materials: Clinical study with inclusion and exclusion criteria defined by an Independent Clinical Committee was carried out. Fifteen patients underwent transcoronary sinus administration with a 15-min occlusion of freshly aspirated and filtered AUBM (60–120 ml). Feasibility was evaluated with Seattle Angina Questionnaire (SAQ), Canadian Cardiovascular Society (CCS) angina classification, perfusion dipyridamole, and coronary angiography. Results: There were no changes in the tolerance parameters. There were no deaths or myocardial infarction during the follow-up. Three patients were readmitted into the hospital. During the follow-up, one patient was diagnosed with cancer of the lung. Improvement of 30% in the quality of life was evaluated by SAQ. The CCS angina classification showed that the mean angina class was 3.0F0.53 at baseline, which improved to 1.6F0.63 at 1 year ( Pb.001). Perfusion imaging (core lab) showed improvement in 12 of 15 patients, with a mean improvement of 40.9% at rest (22 vs. 13) ( Pb.01) and 45.3% at stress (26.5 vs. 14.5) ( Pb.05). Coronary angiography showed more collateral vessels in 10 of 15 patients. Conclusions: We can conclude that AUBM via coronary sinus is feasible in patients with chronic refractory angina after 1 year follow-up, and it appears to be safe.